Unreactive alpha or alpha-theta coma electroencephalogram patterns with favorable neurologic outcomes: a report of three cases and literature review - Marvic Joseph S. Amoranto; Marc Laurence L. Fernandez (Journal of Neurocritical Care)
Background Alpha coma and its variants theta coma and alpha-theta coma (ATC) are clinical coma states characterized by electroencephalographic patterns resembling those of wakefulness. The complete (unreactive) form of these states is invariably associated with poor outcomes among post-anoxic comatose patients. Case Report Herein, we present three adult comatose patients (aged 21, 45, and 51 years) with unreactive ATC patterns, who exhibited remarkable neurological improvement. Two patients experienced post-cardiopulmonary arrest (due to electrocution and viral myocarditis, respectively), while the third had severe septic encephalopathy. Electroencephalograms (EEGs) taken at least 24 hours after coma onset revealed unreactive ATC patterns. All patients survived, achieving significant neurological improvement. Remarkably, in one patient, the only symptom was minor incoordination during ambulation upon discharge. Conclusion These cases challenge the grave prognosis associated with this EEG pattern, particularly in post-anoxic comatose patients. Factors such as younger age, presence of shockable rhythms, and cause of arrest may have contributed to these favorable outcomes.